Global Epidemiology and Antimicrobial Resistance of Klebsiella Pneumoniae Carbapenemase (KPC)-Producing Gram-Negative Clinical Isolates: A Review - Matthew E. Falagas; Christina-Maria Asimotou; Maria Zidrou; Dimitrios S. Kontogiannis; Charalampos Filippou (Microorganisms, 2025)
Klebsiella pneumoniae carbapenemases (KPCs) are a group of class A β-lactamases of Gram-negative bacteria leading to difficult-to-treat infections. We evaluated the global epidemiology of KPC-producing Gram-negative clinical isolates. A systematic search of six databases (Cochrane Library, Embase, Google Scholar, PubMed, Scopus, and Web of Science) was conducted. Extracted data were tabulated and evaluated. After screening 1993 articles, 119 were included in the study. The included studies originated from Asia (n = 49), Europe (n = 29), North America (n = 14), South America (n = 11), and Africa (n = 3); 13 studies were multicontinental. The most commonly reported KPC-producing species were Klebsiella pneumoniae (96 studies) and Escherichia coli (52 studies), followed by Enterobacter cloacae (31), Citrobacter spp. (24), Klebsiella oxytoca (23), Serratia spp. (15), Enterobacter spp. (15), Acinetobacter baumannii complex (13), Providencia spp. (11), Morganella spp. (11), Klebsiella aerogenes (9), Pseudomonas aeruginosa (8), Raoultella spp. (8), Proteus spp. (8), and Enterobacter aerogenes (6). Among the studies with specific blaKPC gene detection, 52/57 (91%) reported the isolation of blaKPC-2 and 26/57 (46%) reported blaKPC-3. The antimicrobial resistance of the studied KPC-producing isolates was the lowest for ceftazidime–avibactam (0–4%). Resistance to polymyxins, tigecycline, and trimethoprim–sulfamethoxazole in the evaluated studies was 4–80%, 0–73%, and 5.6–100%, respectively. Conclusions: The findings presented in this work indicate that KPC-producing Gram-negative bacteria have spread globally across all continents. Implementing proper infection control measures, antimicrobial stewardship programs, and enhanced surveillance is crucial.